PENGARUH KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN PADA PT ASTRA INTERNATIONAL Tbk PERIODE 2013-2022 - Sekar Riana, Putri; Sairin (Journal of Research and Publication Innovation, 2024)
The purpose of this research is to determine the influence of debt policy (DER) and profitability (ROE) on company value (PBV) at PT Astra International Tbk period 2013-2022. The method used is associative quantitative the results of data analysis and hypothesis testing show that DER partially has a significant influence on company value, with a t count of 3.590 which is greater than t table 2,36462 and a significance t of 0,009 < 0,05 An increase in DER causes the company's burden on external parties to become greater On the other hand, ROE does not have a significant effect on company value, with tcount of 0,276 < ttable 2,36462 and t significance of 0,791 > 0,05 The joint influence of DER and ROE simultaneously is also significant on company value, with Fcount of 10,660 > Ftable 4,74 and F significance of 0,008 < 0,05